Treatments of Eye Diseases in Malay Medical Manuscript Ramuan Obat EAP153/9/4 - Mohd Shafri, Mohd Affendi (Journal of Al-Tamaddun, 2021)
The Malay medical manuscript Ramuan Obat EAP153/9/4 is a Malay medical manuscript from Riau Archipelago in today’s Indonesia. It appears to focus on eye diseases and treatments. This study aims to evaluate if the traditional medicines and interventions in the manuscript can be supported scientifically. Critical transliteration and data extraction were performed by applying philological method in identifying and categorising the diseases and interventions. The materia medica was analysed by comparing scientific reports presented in PubMed and Google Scholar, and matching each ingredient to the intended purpose as indicated in the manuscript. The manuscript contains both physical and spiritual interventions amounting to 28 formulations for 7 different types of eye disease. Half of the materia medica and their use in Ramuan Obat EAP153/9/4 could be supported by contemporary scientific evidence. The lack of contemporary scientific evidence for other materia medica, on the other hand, could be attributed to the lack of scientific research on them rather and not necessarily a deficiency in effectiveness. More scientific studies would need to be carried out to validate the safety and efficacy of formulations contained in Malay medical manuscripts as the content could potentially lead to new drug discovery. Apart from scientific gains, the study could also contribute to the preservation of Malay medical culture and heritage.